2018
DOI: 10.1111/jbg.12313
|View full text |Cite
|
Sign up to set email alerts
|

Genetic monitoring of horses in the Czech Republic: A large‐scale study with a focus on the Czech autochthonous breeds

Abstract: We propose the first comprehensive in-depth study monitoring horses in the Czech Republic. We scanned 9,289 animals from 44 populations for 17 equine STRs. Other equids analysed involved Equus przewalskii and Equus asinus. The total of 228 different alleles were detected, with the mean number of 13.4 per locus. The highest allelic richness (AR) was found in the Welsh Part Bred (6.01), followed by the Camargue (5.93) and Czech Sport Pony (5.91), whereas the Friesian exhibited the lowest AR (3.06). Interpopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…The observed heterozygosity for horses of Hucul breed by six loci were higher than the expected heterozygosity which conditioned negative values of the inbreeding index and demonstrated the excess of heterozygotes in this population. The comparison of our results against the data of other researchers of Hucul breed demonstrated that our values of heterozygosity (0.775/0.812) corresponded to the results, obtained for Czech (0.74/8.06) (Putnová L et al, 2018) and Polish Hucul (0.71/9.92) (Mackowski M et al, 2015) and exceeded the results, published for Romanian (0.66/6.58) (Georgescu SE et al, 2008), Austrian, Slovak and Hungarian Huculs (0.71/7.65) (Kusza S et al, 2013). The negative Fis values, determined for Hucul horses by 6 out of 11 microsatellite loci, demonstrated high intrabreed variability and lower heterozygosity (Putnova L et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed heterozygosity for horses of Hucul breed by six loci were higher than the expected heterozygosity which conditioned negative values of the inbreeding index and demonstrated the excess of heterozygotes in this population. The comparison of our results against the data of other researchers of Hucul breed demonstrated that our values of heterozygosity (0.775/0.812) corresponded to the results, obtained for Czech (0.74/8.06) (Putnová L et al, 2018) and Polish Hucul (0.71/9.92) (Mackowski M et al, 2015) and exceeded the results, published for Romanian (0.66/6.58) (Georgescu SE et al, 2008), Austrian, Slovak and Hungarian Huculs (0.71/7.65) (Kusza S et al, 2013). The negative Fis values, determined for Hucul horses by 6 out of 11 microsatellite loci, demonstrated high intrabreed variability and lower heterozygosity (Putnova L et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The average evaluation of inbreeding index was 0.081 ± 0.035 and exceeded the zero value considerably. Thoroughbred, a breed of horses with low diversity, is notable for high average individual coeffi cient of inbreeding which may be related to population bottleneck effect, intense selective pressure or closed conditions of breeding during the long term of the breed history (Vázquez-Armijo JF et al, 2017, Putnová L et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The history of TB horse breeding in a closed Stud Book for three centuries could result in a reduction of the genetic diversity of the TB horses. The relatively high degree of homozygosity in the horses of this breed was confirmed using microsatellite loci by other researchers [13][14][15][16]. Genomic analysis using the 670,000 genotyping array showed that the TB breed had the highest level of homozygosity [6].…”
Section: Discussionsupporting
confidence: 64%
“…The measurement of the actual homozygosity level at the individual and population levels only became possible at the end of the 20th century due to the development of methods for studying genes and DNA polymorphisms. As a result of the widespread use of microsatellite loci in the control of animal origins, this type of highly polymorphic genetic marker has been successfully used to study the genetic features of breeds and their phylogenetic relationships [ 12 , 13 , 14 , 15 ]. The characteristics of the genetic parameters of populations, among which the heterozygosity level is one of the most important, allow us to assess the impact of the breeding system on the level of inbreeding [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand patterns of CNVs between breeds of common ancestral origin, we grouped the breeds in three breed clusters according to the previous PCA analysis ( Fig. 1A; Draught including Exmoor ponies, Warmblood and Friesian horses [26]). The total number of genomic locations presenting SNP CNVs (signal gains and losses) and the percentage of unique SNP CNV gains or losses corresponding to the breed group clusters are shown in Table 3.…”
Section: Breed Cluster Cnv Comparisonsmentioning
confidence: 99%